Evidence‐based guideline for the prevention and management of perioperative infection. Issue 1 (28th February 2023) - Wang, Qiaoyu; Cao, Mingnan; Tao, Hua; Fei, Zhimin; Huang, Xiufeng; Liang, Pixia; Liu, Baiyun; Liu, Jianping; Lu, Xiaoyang; Ma, Penglin; Si, Shuyi; Wang, Shuo; et al.
Abstract: Background: We have updated the guideline for preventing and managing perioperative infection in China, given the global issues with antimicrobial resistance and the need to optimize antimicrobial usage and improve hospital infection control levels. Methods: We conducted a comprehensive evaluation of the evidence for prevention and management of perioperative infection, based on the concepts of the Grading of Recommendations Assessment, Development and Evaluation (GRADE) system. The strength of recommendations was graded and voted using the Delphi method and the nominal group technique. Revisions were made to the guidelines in response to feedback from the experts. Results: There were 17 questions prepared, for which 37 recommendations were made. According to the GRADE system, we evaluated the body of evidence for each clinical question. Based on the meta‐analysis results, recommendations were graded using the Delphi method to generate useful information. Conclusions: This guideline provides evidence to perioperative antimicrobial prophylaxis that increased the rational use of prophylactic antimicrobial use, with substantial improvement in the risk‐benefit trade‐off.